Broadband acoustic pseudospin topological states based on the reverse spin-orbit coupling in generalized insulators - Liu, Chongrui; Lu, Yibing; He, Zhenxin; Guan, Wenliang; Huang, Zhen (Frontiers in Materials, 2024)
Acoustic topological insulators have the excellent characteristic of the pseudospin-dependent one-way transmission of sound edge states immune to back scattering. We realize the broadband acoustic pseudo-spin topological edge states with a sub-wavelength generalized topological insulators, which is achieved by the reverse pseudospin-orbit coupling. By adjusting the topological structure of the scatterers and introducing resonators, the subwavelength band and broadband nontrivial bandgap can be achieved. The results demonstrate that the resonator can significantly reduce the frequencies of p-states and d-states by introducing the resonance scattering; the scattering size and rotation angles change the frequencies of p-states and d-states in opposite direction by adjusting the distribution of sound field. Then we experimentally realize the pseudospin-dependent one-way transmission of sound edge states along the interface separating phononic crystals with distinct topological phase. Our research provides a systematic scheme for the design of acoustic topological insulators with versatile applications.